Inspiration and Exasperation: The Challenges of Inhaled Biologics. (February 2021) - Hall, Peter; Vahle, John L.; Colman, Karyn
The delivery of biotherapeutic molecules (antibodies, proteins, peptides) and nucleic acids via the respiratory route has presented challenges for regulatory approval, due in part to a lack of understanding of the expected pathology, mechanisms of toxicity, and immunogenicity induced by the inhalation route. Although the first inhaled biotherapeutic was approved some time ago (Dornase Alfa, Pulmozyme; Genetech, 1993), no other inhaled biotherapeutics have been marketed for the treatment of human disease other than the inhaled insulins (Exubera; Pfizer, 2006 and Afrezza; Mannkind Corporation, 2014). As a result, scientific knowledge within the toxicologic pathology community is fragmented with precious little publicly available data. Therefore, one of the aims of this special edition was to generate a collection of manuscripts that pathologists and toxicologists could refer in order to understand the pathology, mechanisms of toxicity, immunogenicity, and challenges associated with the development of inhaled biotherapeutics.